The influence of mineral admixtures on the short and long-term performance of concrete - Gonen, Tahir; Yazicioglu, Salih (Pergamon-Elsevier Science Ltd, 2007)
This paper presents a laboratory study on the performance of concrete by adding mineral admixtures, silica fumes (SF) or/and fly ash (FA). Performance of the concrete mixes was determined with short and long-term tests, which include compressive strength, porosity, capillary absorption, wet-dry cycle and accelerated carbonation. The test results, in general, showed that mineral admixtures improved the performance of concretes. SF contributed to both short and long-term properties of concrete, whereas FA shows its beneficial effect in a relatively longer time. As far as the compressive strength is concerned, adding of both SF and FA slightly increased compressive strength, but contributed more to the improvement of transport properties of concretes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: capillary absorption; accelerated carbonation; mineral admixtures; high strength concrete